2022
DOI: 10.1177/09603271211065972
|View full text |Cite
|
Sign up to set email alerts
|

Propofol suppresses proliferation, migration, invasion, and tumor growth of liver cancer cells via suppressing cancer susceptibility candidate 9/phosphatase and tensin homolog/AKT serine/threonine kinase/mechanistic target of rapamycin kinase axis

Abstract: Propofol is a commonly used drug for sedation and general anesthesia during cancer surgery. Previous studies indicate that propofol exerts anti-tumor effect in various cancers. The aim of this study was to investigate the underlying molecular mechanism of propofol in liver cancer. The effects of propofol on liver cancer cells were evaluated by cell viability assay, colony formation assay, and tumor xenograft model. Dysregulated lncRNAs of propofol-treated liver cancer cells were evaluated by transcriptome RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The xenograft model also requires quality control because many cell lines have unknown sources or poorly documented receptor expression, and regulatory safeguards are needed to protect researchers from the high communicability risk from handling human cancer tissue [ 16 , 18 ]. Despite these shortcomings, xenograft models have been used extensively to identify potential molecular mechanisms underlying the observed anti-tumour effects of propofol and local anaesthetics as well as pro- and anti-tumour effects following exposure to inhalational anaesthetics [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Xenograft Modelmentioning
confidence: 99%
“…The xenograft model also requires quality control because many cell lines have unknown sources or poorly documented receptor expression, and regulatory safeguards are needed to protect researchers from the high communicability risk from handling human cancer tissue [ 16 , 18 ]. Despite these shortcomings, xenograft models have been used extensively to identify potential molecular mechanisms underlying the observed anti-tumour effects of propofol and local anaesthetics as well as pro- and anti-tumour effects following exposure to inhalational anaesthetics [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Xenograft Modelmentioning
confidence: 99%
“…Shen et al (2021) showed that propofol could inhibit the proliferation, invasion and apoptosis of ovarian cancer cells through the lncRNA HOST2/JAK2/STAT3 axis. Chang et al (2022) reported that propofol exerted an antitumor effect by down-regulating lncRNA CAS9, thereby inhibiting the Akt/mTOR signaling pathway in hepatocellular carcinoma. In colon cancer, propofol promoted cell apoptosis and inhibited distant metastasis through the activation of WIF-1 and inhibition of Wnt signaling pathway by negatively regulating the expression of lncRNA HOTAIR (Zhang et al, 2020a).…”
Section: Propofol and Lncrnasmentioning
confidence: 99%
“…[10][11][12][13] Some anesthetic medications, including sevoflurane, dexmedetomidine, and propofol, may have some impact on the malignant phenotype of tumor cells. [14][15][16] These anesthetics are thought to be potential tumor suppressors or facilitators; however, it is still unknown how they will affect glioma patients. Sevoflurane and propofol are frequently used anesthetics in therapeutic settings.…”
Section: Introductionmentioning
confidence: 99%